MicroRNA-337 inhibits cell proliferation and invasion of cervical cancer through directly targeting specificity protein 1 - Wei Dong; Baosheng Li; Juan Wang; Yipeng Song; Zicheng Zhang; Chengrui Fu (Tumor Biology, 2017)
Cervical cancer is the fourth most commonly occurring malignancy in females worldwide. Accumulated studies have demonstrated that the aberrant expression of microRNAs plays important roles in tumorigenesis and tumor development and potentially serves as therapeutic targets in various cancers including cervical cancer. Therefore, the identification of specific microRNAs contributed to cervical cancer formation and progression would provide critical clues for the treatments for patients with this disease. In this study, we aimed to detect microRNA-337 expression pattern and investigate the biological roles of microRNA-337 in the regulation of the malignant phenotypes of cervical cancer and its underlying mechanisms. We found that microRNA-337 expression was significantly downregulated in cervical cancer tissues and cell lines. In addition, its aberrant expression levels were positively correlated with tumor size, International Federation of Gynecology and Obstetrics stage, and lymph node metastasis of cervical cancer. The ectopic expression of microRNA-337 suppressed cell proliferation and invasion of cervical cancer in vitro. Furthermore, specificity protein 1 was identified as a direct target of microRNA-337 in cervical cancer. The expression of specificity protein 1 increased in cervical cancer tissues and negatively correlated with microRNA-337 expression level. Moreover, rescue experiments revealed that upregulation of specificity protein 1 could rescue the effects of microRNA-337 on cervical cancer cells. Taken together, these findings collectively demonstrate that microRNA-337 exerts its tumor-suppressing roles in cervical cancer by directly targeting specificity protein 1, thereby indicating a potential novel potential therapeutic target for patients with cervical cancer.